2017
DOI: 10.1149/07801.1979ecst
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Infiltration into SOFC Cathode Backbones

Abstract: Intermediate Temperature Solid Oxide Fuel Cells (IT-SOFCs) with yttrium stabilized zirconia electrolyte were fabricated by the impregnation of nanoparticle promoters into specific backbone cathodes: electronic conductor La 0.8 Sr 0.2 MnO 3 , ionic conductor Sm 0.2 Ce 0.8 O 2-δ and mixed ionic and electronic conductor Nd 1.95 NiO 4+δ. The electrochemical performances of the symmetrical half-cells and single cells were improved using impregnated cathodes. The electrochemical measurements showed that a MIEC backb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The sample is sintered at elevated temperatures so that the infiltrate particles can crystalize and bond to the backbone electrode. In some cases, the temperature for crystallization can be lower compared to its stand‐alone powder synthesis process, depending on the precursor 16–19 . As a common practice, La 1‐ x Sr x Co 1− y Fe y O 3− δ (LSCF) cathode is infiltrated with ceria‐based electrolyte materials.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample is sintered at elevated temperatures so that the infiltrate particles can crystalize and bond to the backbone electrode. In some cases, the temperature for crystallization can be lower compared to its stand‐alone powder synthesis process, depending on the precursor 16–19 . As a common practice, La 1‐ x Sr x Co 1− y Fe y O 3− δ (LSCF) cathode is infiltrated with ceria‐based electrolyte materials.…”
Section: Surface Modification Methodsmentioning
confidence: 99%
“…In some cases, the temperature for crystallization can be lower compared to its stand-alone powder synthesis process, depending on the precursor. [16][17][18][19] As a common practice, La 1-x Sr x Co 1−y Fe y O 3−δ (LSCF) cathode is infiltrated with ceria-based electrolyte materials. SDC nanoparticles phase is formed and uniformly distributed on the surface of an LSCF backbone.…”
Section: Infiltration/impregnationmentioning
confidence: 99%
“…Using a nanosized second phase with ionic conduction also provides more reaction sites and speeds up the kinetics of the reactions . To date, numerous studies have been done on the effect of different nanocatalyst infiltration into the LSM air electrode backbone in SOCs . For instance, it has been shown that infiltration of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3− δ (BSCF) into the LSM backbone causes a 12 times decrease in the polarization resistance of air electrodes at 800°C .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 To date, numerous studies have been done on the effect of different nanocatalyst infiltration into the LSM air electrode backbone in SOCs. [7][8][9][10][11][12][13][14] For instance, it has been shown that infiltration of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3−δ (BSCF) into the LSM backbone causes a 12 times decrease in the polarization resistance of air electrodes at 800°C. 7 Although LSM is one of the most studied materials in the air electrode cases, the anodic polarization behavior is less investigated.…”
Section: Introductionmentioning
confidence: 99%